Work and life balance – the new age management matter - Apsite, Annija (University of Latvia, 2019)
Even apart from the dramatic statistical data about sicknesses caused by imbalance and burnout, surveys make it clear that individuals are struggling to enjoy living because of the growing workload and the persistent presence of technologies around us (EQLS, 2016). Work-life imbalance causes loss for companies for several reasons - intentional or unintentional absence at work, high employee turnover, low productivity, insurance costs etc. The scientific question arises from the fact that until now there have not been clear researches which indicate the model of how the work and life balance (WLB) or imbalance is being created. Particularly, author is interested in how the interaction between the values of employee and employer or direct supervisor affects WLB of the employee. However, before practical research the aim of this paper is to evaluate the importance of this topic in Latvia and to detect the major steps to even the balance out between work and private life by using the data that is already available. The methodology of the research is to gather local (i.e. TNS) and international (i.e.EUROSTAT) secondary data available to assess the current situation in Latvia. The research shows that unemployed people in Latvia tend to feel less stressed than those who are employed, which shows that although unemployment itself may cause stress, workplace and employment creates even a greater room for stress related factors. Further author is determined to conduct a research to later provide a model, which could be practically used by managers to help them with managing the WLB for their employees.
Keywords: work-life balance; job satisfaction; stress; Research Subject Categories::SOCIAL SCIENCES::Business and economics